Acknowledgement to Reviewers of Pharmaceutics in 2014 - Pharmaceutics Editorial Office (MDPI AG, 2015)
The editors of Pharmaceutics would like to express their sincere gratitude to the following reviewers for assessing manuscripts in 2014:[...]